2016
DOI: 10.3390/molecules21081033
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Suppresses HUVECs Cell Injury Induced by Oxidative Stress through Activating the Nrf2 Signaling Pathway

Abstract: Abstract:Oxidative stress plays an important role in the pathogenesis of cardiovascular diseases. Salidroside (SAL), one of the main effective constituents of Rhodiola rosea, has been reported to suppress oxidative stress-induced cardiomyocyte injury and necrosis by promoting transcription of nuclear factor E2-related factor 2 (Nrf2)-regulated genes such as heme oxygenase-1 (HO-1) and NAD(P)H dehydrogenase (quinone1) (NQO1). However, it has not been indicated whether SAL might ameliorate endothelial injury ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…SDS exhibits a wide spectrum of pharmacological effects [9], including anti-oxidative, anti-fatigue, anti-cancer, anti-apoptosis, and anti-inflammatory effects [10]. In addition, SDS has been shown to have cytoprotective and angiogenic effects on human bone marrow-derived endothelial progenitor cells through the Akt/mammalian target of rapamycin (mTOR)/p70S6K/MAPK signaling pathways [11]. As a key molecular pathway, the Wnt/β-catenin signaling pathway regulates neuronal survival and development of the central nervous system [12].…”
Section: Introductionmentioning
confidence: 99%
“…SDS exhibits a wide spectrum of pharmacological effects [9], including anti-oxidative, anti-fatigue, anti-cancer, anti-apoptosis, and anti-inflammatory effects [10]. In addition, SDS has been shown to have cytoprotective and angiogenic effects on human bone marrow-derived endothelial progenitor cells through the Akt/mammalian target of rapamycin (mTOR)/p70S6K/MAPK signaling pathways [11]. As a key molecular pathway, the Wnt/β-catenin signaling pathway regulates neuronal survival and development of the central nervous system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that ROS are the major initiators of myocardial damage in myocardial I/R injury and the attenuation of oxidative stress in myocardial cell has been demonstrated to improve myocardial function following ischemia (4,33). It has been demonstrated that salidroside may suppress oxidative stress-induced endothelial dysfunction, cardiomyocyte injury and necrosis, and cerebral ischemia/reperfusion injury, through decreasing excessive ROS generation and improving mitochondrial function (34)(35)(36)(37). However, the effect of salidroside in myocardial I/R injury-induced oxidative stress has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In resting cells, Nrf2 is rapidly degraded in the cytosol through the ubiquitin-proteasome system [27]. When the endothelial cells are exposed to various antioxidants, the Nrf2-Keap1 interaction is disturbed, thus preventing proteasome-dependent degradation, allowing the nuclear accumulation of Nrf2 and activating the expression of cytoprotective genes [27][28][29]. It should be stressed that, even though the most described mechanism for pharmacological activation of Nrf2 is focused on proteasome inhibition, the tight control of Nrf2 level and activity involves not only proteasomal degradation but also transcription, translation and post-translational modifications [27].…”
Section: Discussionmentioning
confidence: 99%